2020
DOI: 10.1177/1179173x20972728
|View full text |Cite
|
Sign up to set email alerts
|

Do Social Inequalities in Smoking Differ by Immigration Status in Young Adults Living in an Urban Setting? Findings From the Interdisciplinary Study of Inequalities in Smoking

Abstract: Objectives: We assessed whether social inequalities in smoking observed among young adults born in Canada were also apparent in same-age immigrants. Methods: Data were drawn from an investigation of social inequalities in smoking conducted in an urban setting (Montreal, Canada). The sample included 2077 young adults age 18 to 25 (56.6% female; 18.9% immigrants who had lived in Canada 11.6 (SD 6.4) years on average). The association between education and current smoking was examined in multivariable logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Similarly, some research has shown that foreign-born healthier individuals with higher socio-economic status tend to stay in their home countries [31]. A second potential explanation is that some studies have found that parents' health behaviors and higher parental monitoring of children may be responsible for lower prevalence of tobacco product use in foreign-born adolescents and young adults [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some research has shown that foreign-born healthier individuals with higher socio-economic status tend to stay in their home countries [31]. A second potential explanation is that some studies have found that parents' health behaviors and higher parental monitoring of children may be responsible for lower prevalence of tobacco product use in foreign-born adolescents and young adults [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Some research has shown that foreign-born healthier individuals with higher socio-economic status tend to stay in their home countries [31]. Second, some authors have found that parents' healthy behavior approach and higher parental monitoring for their children may be responsible for lower prevalence tobacco product use in foreign-born young adults [31,32].…”
Section: Discussionmentioning
confidence: 99%